2020
DOI: 10.1080/15476286.2020.1836456
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of key long non-coding RNAs in the mouse cochlea

Abstract: The auditory system is a complex sensory network with an orchestrated multilayer regulatory programme governing its development and maintenance. Accumulating evidence has implicated long noncoding RNAs (lncRNAs) as important regulators in numerous systems, as well as in pathological pathways. However, their function in the auditory system has yet to be explored. Using a set of specific criteria, we selected four lncRNAs expressed in the mouse cochlea, which are conserved in the human transcriptome and are rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…12 Studies have shown that specific lncRNAs can be expressed in different cell types of the auditory system, with distinct expression patterns and variation. 13 The human auricle is supported by ear cartilage. When the ear cartilage is dysplastic, it may lead to auricle deformities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Studies have shown that specific lncRNAs can be expressed in different cell types of the auditory system, with distinct expression patterns and variation. 13 The human auricle is supported by ear cartilage. When the ear cartilage is dysplastic, it may lead to auricle deformities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNAs generally exist in the sensory epithelial cells of the mouse inner ear during the development of the auditory system, thereby contributing to the regulation of the development of the auditory system 12. Studies have shown that specific lncRNAs can be expressed in different cell types of the auditory system, with distinct expression patterns and variation 13…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs, such as Lockd, Dlx1as, Emx2os, and Soxot, are of interest because they are located in unresolved deafness-associated loci (Ushakov et al, 2017). Additionally, recent studies have begun to hypothesize roles for some lncRNAs in the inner ear, including Gas5, which may regulate the Notch1 pathway (Koffler-Brill et al, 2021). miRNAs have specific spatiotemporal expression in the auditory and vestibular systems, with some having known roles in inner ear development and function (Friedman et al, 2009;Rudnicki et al, 2014;Mahmoudian-sani et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…A handful of studies have characterized the expression profiles of lncRNAs in the inner ear by using high-throughput sequencing technologies ( 83 , 105 , 147 , 164 , 176 ). Some inner-ear lncRNAs are also expressed in other systems, such as Malat1 , while others, such as Xloc_012867 , are novel lncRNAs that are apparently restricted to the inner ear ( 83 ).…”
Section: The Noncoding Genome and The Inner Earmentioning
confidence: 99%
“…A handful of studies have characterized the expression profiles of lncRNAs in the inner ear by using high-throughput sequencing technologies ( 83 , 105 , 147 , 164 , 176 ). Some inner-ear lncRNAs are also expressed in other systems, such as Malat1 , while others, such as Xloc_012867 , are novel lncRNAs that are apparently restricted to the inner ear ( 83 ). A study identified the lncRNA Rubie as a candidate for circling behavior in mice, as it is expressed in the cochlea at embryonic stages and is found in close proximity to Bmp4, potentially regulating it in cis ( 138 ).…”
Section: The Noncoding Genome and The Inner Earmentioning
confidence: 99%